An Ubuntu-based reflection on the public health impact of silica dust exposure in the South African mining industry - Angeline Mojakwana; Cornelius Ewuoso (Inishmore Laser Scientific Publishing Ltd, 2023)
Issuing fitness certificates to South African mine workers with early and mild silicosis to continue risk work underground is a public health concern. This article draws on the view of solidarity to contend this practice. We employed a normative ethics approach and the concept of solidarity in African 'Ubuntu' philosophy to report and reflect on the public health implications of silica dust exposure among South African miners. We argued that since silicosis is irreversible, incurable, and could be progressive, leading to death, thus, issuing certificates of fitness to individuals who have early and mild silicosis, in many ways, is inappropriate and the practice ought to be rejected. We recommend more studies to reflect on the ethical management of silica dust exposure in the South African gold mining industry.